Party and Protest Political Participation among Students in Western and Central-Eastern Europe - Oana, Ioana-Elena (PARTECIPAZIONE E CONFLITTO, 2019)
This paper aims to bridge the literature on students' socio-political attitudes with the wider literature on political participation that previously focused on cross-regional differences in participation rates and on varied forms of participation more generally. In doing so, the paper extends the empirical scope of previous analyses by exploring, on the one hand, the extent to which student political participation varies across wide ranges of both party- and protest-related activities; and, on the other hand, by looking at differences in student and non-student participation across 6 countries – 4 old democracies in Western European (WE) and 2 post-communist democracies in Central-Eastern Europe (CEE). Methodologically, the paper combines a quasi-experimental design based on genetic matching with regression models in order to better isolate the effect of student status on political participation from that of age, gender, and family background. Using original survey data gathered within the framework of the POLPART Project among 6,990 respondents, the results for both WE and CEE suggest that students do not significantly differ from non-students in terms of political participation when they are matched on age, gender, and family background. Additionally, when controlling for other variables commonly associated with political participation, such as political interest, students actually appear to engage in party politics less than their non-student counterparts. This indicates that existing college-effects models focusing on the impact of being a student on socio-political attitudes are, at best, spurious. When matching and formally comparing stu-dents in WE and in CEE, CEE students appear to be more engaged than their WE counterparts. This indicates that the "apathetic" and "atomistic" perspective on CEE political engagement might not hold for more recent years, especially when it comes to Romania.